Comparison of second-line treatment outcomes between sensitive and refractory small cell lung cancer patients: a retrospective analysis - YUMUK, PERRAN FULDEN (SPRINGER INTERNATIONAL PUBLISHING AG, 2013)
Small cell lung cancer (SCLC) has a high relapse rate despite being very chemosensitive. The efficacy of second-line treatment is dismal. Our aim was to evaluate the outcome of second-line treatment. We retrospectively assessed data of 120 SCLC patients who failed first-line treatment and received second-line treatment at three medical oncology centers. Median age of group was 58. 82 % had an ECOG PS of 0-1 at the time of relapse. 39 % were at limited stage (LS) at the time of diagnosis. Patients who progressed more than 3 months after first-line therapy were categorized as having platinum-sensitive disease (PSD) (64 %). The number of patients who received platin-based combination treatment was 33 (27 %). The median OS time starting from the initiation of second-line treatment was 7 months. Multivariate analysis identified PS (p = 0.006), extent of disease at diagnosis (0.014) and PSD (0.001) as the independent prognostic factors for survival. Subgroup analyses of the patients with PSD indicated platin rechallenge yields higher progression-free survival, overall survival and overall response rate. Patients with good ECOG PS,who have PSD or initially presenting with LS, have a good prognosis and in patients with PSD, platinum-based therapy would be more appropriate.
Keywords: Platinum sensitive disease; Platinum refracter disease; Second-line chemotherapy; Small cell lung cancer; PHASE-II; TOPOTECAN; CHEMOTHERAPY; ETOPOSIDE; CISPLATIN; PROGRESS; THERAPY; TRIAL; CARE